Effectiveness of Subsidised Fertilizer Distribution on Corn Farming in South Ogan Komering Ulu District - Saputri, Emaliana; Munajat, Munajat; Sari, Yunita (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2022)
The main objective of this study was to analyze the effectiveness of the distribution of subsidized fertilizers in corn farming in the South OKU District. Analyzing the effectiveness of subsidized fertilizer distribution is to use the scoring method and to see the correlation between the effectiveness of subsidized fertilizer distribution and corn production, the Spearman correlation coefficient is a nonparametric statistic. Based on the results of the study, it was found that the average level of effectiveness of the six indicators was 75.25%. From the results of the percentage of the six indicators that are greater than 61% and less than 80%, the fertilizer subsidy policy of the South OKU District is said to be quite effective. The relationship between the effectiveness of the distribution of subsidized fertilizers on corn production in South OKU District. there is no significant relationship with a significance value greater than the value, which is 0.336>0.05. Based on the results of the correlation test of the effectiveness of the distribution of subsidized fertilizers with corn production, the indicators of price effectiveness and type have a unidirectional relationship. While the indicators of the effectiveness of place, time, quality, and quantity have a non-unidirectional relationship.